2020
DOI: 10.3390/nu12061641
|View full text |Cite
|
Sign up to set email alerts
|

Plate Waste Generated by Spanish Households and Out-of-Home Consumption: Results from the ANIBES Study

Abstract: Food waste is a major environmental issue that must be tackled in order to achieve a sustainable food supply chain. Currently, in Spain there are no studies that examine the amounts and sources of plate waste (PW) produced by both household and out-of-home consumption. The present study aims to provide this information from a representative sample from the Spanish population. A total of 2009 individuals aged 9–75 years, from the ANIBES study (“anthropometric data, macronutrients and micronutrients intake, prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
2
6
0
4
Order By: Relevance
“…For example, a study about food waste at the household level in the Netherlands revealed that increasing age had a diminishing impact [44]. Furthermore, according to the ANIBES study, household plate waste generated by Spanish consumers [45] and the amount of food waste (mostly generated by cooking excessive amounts) in Hungarian households decreases with age [46]. In contrast, in some studies age did not have significant influence [47,48].…”
Section: The Relationship Between Socio-demographic Data and Environmental And Political Determinants Of Food Choicesmentioning
confidence: 99%
“…For example, a study about food waste at the household level in the Netherlands revealed that increasing age had a diminishing impact [44]. Furthermore, according to the ANIBES study, household plate waste generated by Spanish consumers [45] and the amount of food waste (mostly generated by cooking excessive amounts) in Hungarian households decreases with age [46]. In contrast, in some studies age did not have significant influence [47,48].…”
Section: The Relationship Between Socio-demographic Data and Environmental And Political Determinants Of Food Choicesmentioning
confidence: 99%
“…The existing literature suggests that human decision-making is highly complicated. The subjective and objective characteristics, including demographic and economic factors [18], diet culture [6,36], social rules [37], perceptions [19], attitudes [38,39], dining factors [40], information intervention [9,11], and other factors can affect food-wasting behavior. However, it was found that the impact of the above-listed factors is not consistent under different circumstances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second issue was to determine how to obtain food waste data. To date, food diaries and second-hand data methods [27], visual estimation [33], self-report [34], the photography method [18], and the direct weighing methods have been used [17,39]. The direct weighing method is more objective, accurate, and reliable than the others [16,45].…”
Section: Data Sources and Collectionmentioning
confidence: 99%
See 2 more Smart Citations